How teachers’ caring behavior impacts the socio-cultural adaptability of international students: a chain mediation model - Yin, Zilong; Zhao, Yuhao; Wang, Yuefang (Frontiers in Psychology, 2025)
Enhancing socio-cultural adaptability (SCA) is critical to improving the educational quality of international students. Guided by cultural adaptation theory, this study tested whether teachers’ caring behavior (TCB) promotes SCA in online education and examined the mediating roles of perceived social support (PSS) and resilience (RS). A sample of international students (N = 872) completed validated scales for TCB, PSS, RS, and SCA; data were analyzed with SPSS 27.0 and AMOS 21.0 using stratified linear regression and mediation models. Results showed that TCB significantly and positively predicted SCA, RS partially mediated the TCB–SCA association, and PSS affected the TCB–SCA relationship only indirectly through RS. These findings clarify the interplay among TCB, PSS, RS, and SCA in online settings and provide theoretical and practical guidance for interventions that enhance international students’ SCA by strengthening resilience and supportive environments.